Positive business reputation formation as a challenge of organizational behavior - Shavkun, Iryna; Dybchinska, Yana (Management and Entrepreneurship: Trends of Development, 2023)
The paper provides a critical overview of different conceptions concerning positive business reputation formation. Hence, the aim of the study is to explore the impact of organizational behavior on building positive business reputation as one of the main tasks of chief executive offices. This research employed a qualitative method to obtain a comprehensive understanding of corporate reputation as an intangible and critical asset in sustaining business operations, its formation being a challenge of organizational behavior management. The topicality of the investigation problem makes it necessary to analyze the effect of organizational behavior on company’s performance as far as managing business reputation in conditions of growing expectations by versatile stakeholder groups. Among the main determinants of business reputation management risks is insufficient internal and external communication between various functions and structures, with their own, sometimes contradictory, beliefs and expectations. When expectations change and the nature of the company remains the same, the gap between reputation and reality widens and risks increase. No less important is the responsibility of management for the formation and protection of business reputation, as well as the possession of appropriate methods and tools for measuring reputational risk. The issue of a robust causal link between the behavior and reputation of a company becomes even more obvious in the process of developing staff loyalty. A refined synthesis of the literature on the relationship between employee loyalty and organizational performance in the context of risk management highlights various indicators of employee loyalty to the company and organizational performance. However, the problem of managerial levers that can consolidate or improve organizational efficiency requires further research. The results obtained show that employee loyalty is a strategic tool of organizational behavior management to increase the organization’s bottom line. This research contributes to staff loyalty management as a process that allows the organization to optimize its human capital, increase the efficiency of the organization performance and the personnel involvement in the work, that is, to form high-level staff loyalty. JEL Classification: J24, E22, M12, M14, D23, O 15.